Platinum-based neoadjuvant chemotherapy upregulates STING/IFN pathway expression and promotes TILs infiltration in NSCLC - Gao, Huan; Zhang, Xiaoni; Ren, Mengdi; Jiang, Aimin; Liu, Na; Wang, Jingjing; Zheng, Xiaoqiang; Liang, Xuan; Ruan, Zhiping; Tian, Tao; Fu, Xiao; Yao, Yu (Frontiers in Oncology, 2024)
Objectives To evaluate the effects of platinum-based neoadjuvant chemotherapy (NACT) on the STING/IFN pathway and tumor-infiltrating lymphocytes (TILs) in non-small cell lung cancer (NSCLC), as well as clinicopathological factors affecting patient survival. Materials and methods A total of 68 patients aged 34-77 years with NSCLC who received neoadjuvant chemotherapy and surgical treatment from March 2012 to February 2019 were reviewed, and the clinical pathological data and paired tissue specimens before and after NACT were collected. Immunohistochemistry and immunofluorescence were used to detect the protein levels of STING, PD-L1 and IFN-β, and the infiltration density of CD3+ TILs and CD8+TILs. The correlation between the expression of STING, PD-L1, IFN-β and the infiltration density of CD3+ TILs and CD8+ TILs as well as the clinicopathological characteristics before and after NACT was analyzed. The relationship between the related indexes, clinicopathological features and prognosis was also discussed. Results NACT increased the expression of STING, IFN-β and PD-L1 in tumor cells, and the infiltration of CD3+ and CD8+ TILs. In addition, ypTNM stage, ypN stage, changes in CD3+ TILs and in PD-L1 were associated with DFS (disease-free survival). CD3+ TILs changes and ypN stage were associated with OS (overall survival). Notably, ypN stage and CD3+ TILs changes were independent prognostic factors for DFS and OS. Conclusion NACT stimulates STING/IFN-β pathway, promotes infiltration of CD3+ and CD8+ TILs, triggers innate and adaptive immunity, and also upregulates PD-L1, which complemented the rationale for neoadjuvant chemotherapy in combination with immunotherapy. In addition, DFS was longer in patients with ypTNM I, ypN0-1, and elevated CD3+TILs after NACT. Patients with ypN0 and elevated CD3+ TILs after NACT had better OS benefits.